The functions of grand juries in criminal cases - Monahan, James H. (Statistical and Social Inquiry Society of Ireland, 1865)
The various branches of our criminal procedure are necessarily closely interwoven. The necessity or the usefulness of a particular step in the complex process by which criminals are brought to justice, is often dependent on, and inexplicable without, reference to the mode in which previous and subsequent stages of the investigation art conducted It is therefore impracticable to form a judgment as to the value, or uselessness, of any detail of the structure of our criminal procedure, without having previously acquired a conception of the entire procedure?from the accusation to the conviction?as a whole. And in order to confine the discussion of such a subject within reasonable limits, we must assume that the principal features of the rest of the machinery are to be regarded as practically unchangeable.
Read Tuesday, 20th June, 1865
Keywords: Grand juries; Criminal prosecution procedure; 314.15